If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -13 = 5x + 5 Reorder the terms: -13 + 8x = 5x + 5 Reorder the terms: -13 + 8x = 5 + 5x Solving -13 + 8x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -13 + 8x + -5x = 5 + 5x + -5x Combine like terms: 8x + -5x = 3x -13 + 3x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 -13 + 3x = 5 + 0 -13 + 3x = 5 Add '13' to each side of the equation. -13 + 13 + 3x = 5 + 13 Combine like terms: -13 + 13 = 0 0 + 3x = 5 + 13 3x = 5 + 13 Combine like terms: 5 + 13 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 5x+36=8x+12 | | 8x+9=3x+29 | | 7x-16=68 | | 73-3x=15x+15 | | 9-7x=81-35x | | 9x-5=22 | | 4x-7-8=32 | | -7y=-84 | | 34n=91.8 | | 4(a-2)=3(a+2) | | 3m=22.8 | | 1.6t=32 | | -4n=-20 | | 5m=-470 | | x-1+2x-2+3x-3=30+4x | | 36+x=-2 | | 3x-y-2=0 | | x-65=-5 | | 5+ax=12-bx | | -9-3x=12-10x | | 5y=45 | | x-23=49 | | 6x+36=15x-63 | | 3y+2.5x-3.4=0 | | 3y+2.5x-3.4= | | 231-6x=30x+23 | | 65x+10=15 | | 6-10x=206-45x | | 6-10x=206-4x | | 4x+12=-87-7x | | 142-6x=5x+10 | | 244d=244 |